2002
DOI: 10.1017/s0267190502000090
|View full text |Cite
|
Sign up to set email alerts
|

9. Peer-Peer Dialogue as a Means of Second Language Learning

Abstract: From the theoretical perspective of a sociocultural theory of mind, cognition and knowledge are dialogically constructed. Embedded in this theoretical framework, this chapter reviews research studies in which peer-peer dialogue is linked to second language learning as students engage in writing, speaking, listening and reading activities. The review takes the stance that the type of dialogue of particular significance in the language learning process is collaborative dialogue, or that which occurs when learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(132 citation statements)
references
References 0 publications
3
119
0
10
Order By: Relevance
“…Thus, it is possible for peers with almost equal ability to provide social mediations for other learners. Other confirming research examining peer dialogue (Ohta 2000, Swain, Brooks andTocalli-Beller 2002) showed that by requesting help from other peers and offering advice, the participants positioned themselves as experts and novices throughout the interactions. Together, they could achieve a level of performance beyond their individual level of competence (Ohta 2000).…”
Section: Resultsmentioning
confidence: 94%
“…Thus, it is possible for peers with almost equal ability to provide social mediations for other learners. Other confirming research examining peer dialogue (Ohta 2000, Swain, Brooks andTocalli-Beller 2002) showed that by requesting help from other peers and offering advice, the participants positioned themselves as experts and novices throughout the interactions. Together, they could achieve a level of performance beyond their individual level of competence (Ohta 2000).…”
Section: Resultsmentioning
confidence: 94%
“…This proves the usefulness of such an activity to raise students' language awareness, which is also reflected in the following two instances of collaborative dialogue and metatalk (cf. Swain et al, 2002) These two extracts from discussions students led on Voxopop focus on the linguistic output itself. The student who commented on the original contribution had picked up on certain aspects of the other student's language and now enquired about them.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate that teachers, through their interactions with students, mediate between the students' current linguistic levels in English and their commonsense understandings of science, on the one hand, and the educational discourse and specialist understandings of the subject, on the other. Swain, Brooks, & Tocalli-Beller (2002) pointed out that collaborative dialogue is beneficial in language learning because when learners encounter linguistic problems, the dialogue can help them to solve the problems together.…”
Section: Interactions In Non-english Major Large Classes In Vietnammentioning
confidence: 99%